(untitled) (قضايا سياسية, 2024)
The issue of energy security is among the important topics, because the continuity and vitality of the economy depends on: energy, of its various types, including oil, which is a source of energy and a raw material used in various industrial sectors. Countries are concerned with the issue of energy security, and are working to provide guarantees and provide alternatives, whether in terms of the countries from which they import, or in terms of the multiplicity of energy sources. The Russian-Ukrainian war caused relative damage to energy security, before the world moved to contain it, and among the important tools for dealing with that issue was: OPEC. OPEC is an organization that includes a number of major oil producers in the world, and has flexibility to increase production, and has dealt with war events in a way that does not lead to targeting the rights of producers, or increasing the energy crisis. The aim of this research is to know the role of OPEC in: providing energy security guarantees, in order to achieve global stability.